Item Analysis Using Rasch Model in Semester Final Exam Evaluation Study Subject in Physics Class X TKJ SMK Negeri 2 Manokwari - Jefri Palimbong; Mujasam Mujasam; Alberto Yonathan Tangke Allo (Kasuari: Physics Education Journal (KPEJ), 2018)
The purpose of this research is to item analyze in semester final exam evaluation using Raschmodel in terms of validity, reliability, and difficulty level study subject in physics class X TKJ SMK Negeri 2Manokwari. This research was a qualitative research that is evaluation of learning outcomes usingquantitative descriptive method with data collection techniques used documentation. The data of respondents44 students with the number of items 30 questions, obtained the result are the validity of the conformity levelof item 26 questions was fit and 4 questions not fit. The students reliability 0,37 is weak, the item reliability0,83 is good and the reliability between students with item 0,42 is bad. The difficult level of item general inthe medium category, the means is very good because it is not difficult and not easy. The conclusion itemanalysis using rasch model in semester final exam evaluation were valid, reliable, and the difficulty level ofitem is very good.